Physical activity during and after breast cancer therapy and associations of baseline physical activity with changes in cardiac function by echocardiography - Upshaw, Jenica N. (Cancer Med, 2020)
BACKGROUND: Observational studies suggest that regular physical activity may reduce cardiovascular morbidity and cancer recurrence in survivors of breast cancer. The association between physical activity and cardiac function with breast cancer therapy is unknown. METHODS: Self‐reported physical activity was assessed using the Godin Leisure‐Time Exercise Questionnaire at repeated intervals in a longitudinal cohort study of 603 breast cancer participants treated with doxorubicin and/or trastuzumab. Multivariable regression models estimated associations between clinical variables and physical activity. Generalized estimating equations adjusted for prespecified variables estimated associations between baseline physical activity and longitudinal echocardiographic measures of systolic and diastolic function. RESULTS: Physical activity was low at baseline, prior to cancer therapy initiation. More than half of participants reported no moderate‐strenuous physical activity, and only 12.1% met guideline recommended levels of physical activity. Physical activity increased after chemotherapy completion; however, only 26.0% of individuals were sufficiently active 3 years after cancer diagnosis. Body mass index, hyperlipidemia and higher cancer stage were significantly associated with lower total physical activity at baseline. Higher baseline physical activity was very modestly associated with an attenuation in the absolute decline in left ventricular ejection fraction over time (β 0.4%, 95% CI 0.1, 0.7, P = .02 for each 10‐unit increase in total activity). There tended to be a cardioprotective association with cardiotoxicity risk, although this was not statistically significant (HR 0.83, 95% CI 0.66, 1.04, P = .097). CONCLUSIONS: A small proportion of breast cancer patients and survivors are engaged in regular moderate‐strenuous physical activity. While only modest associations between self‐reported physical activity and left ventricular systolic function were observed, our findings do not exclude a cardioprotective benefit of exercise.